POLA ASUH PETANI SAYUR TERHADAP ANAKNYA DI KELURAHAN MAHARATU KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Putra, Aza Juliansyah; Natuna, Daeng Ayub; Achmad, Said Suhil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research was initiated against the backdrop with a pattern of asuh that runs on vegetable farmers who intend to use for their child in Kelurahan Maharatu Kecamatan Marpoyan Damai Kota Pekanbaru. Because foster pattern interpreted as is a educator deliver and directing will (desire) a son at good. Formulation problems this research is how baik-buruk foster pattern farmers vegetable for their child in Kelurahan Maharatu Kecamatan Marpoyan Damai Kota Pekanbaru?. The purpose of this research is to know baik-buruk a pattern asuh that runs on vegetable farmers who intend to use for their child in Kelurahan Maharatu Kecamatan Marpoyan Damai Kota Pekanbaru. pulation in this study as much as 80 people.Included in this study use the model nonprobability sampling to technique sampling quotas the technique to determine samples from population to have certain number of (quotas) desirable. Technique the data in this research is a technique chief, which consisted of 75 statement. Data is collected of the respondents who were 39 the farmers vegetable farmers vegetable for a sample of research and 30 people farmers vegetable for testing. After chief in testing , there are 3 items that invalid , and researchers throw all that is not valid , so that the whole instrument expressed reliabel as alpha cronbach = 0,97. The findings of the research indicated that the custody of vegetable farmers for their child in urban village in pekanbaru maharatu marpoyan peace have good.Key Words: Foster Pattern, Foster Pattern Farmers Vegetable For Their Child